UJI AKTIVITAS ANTIOKSIDAN DAN DETERMINASI TOTAL FLAVONOID DAN TOTAL FENOL DARI EKSTRAK BATANG RAMBUSA (Passiflora foetida L.) - Monica Suryani; Sondang Purba; Tumpak Rudi Aman Manik; Sarah Anisa (Universitas Sari Mutiara Indonesia, 2021)
Oxidative stress caused by free radicals can trigger various dangerous diseases, such as cancer, degenerative diseases, cardiovascular disease, and others. Substances that can counteract or prevent these free radicals are antioxidants which are said to have therapeutic value against these diseases. The plant that will be used in this study is Rambusa stem (Passiflora foetida L.) which is useful as a medicine to treat bones, anemia, cancer, lower blood pressure, kidney disorders, and relieve stress. The purpose of this study was to determine the secondary metabolites found in Rambusa stems, and determine the strength of the antioxidant activity of Rambusa stems in trapping free radicals (DPPH). The extraction method was carried out by maceration using 96% ethanol solvent, phytochemical screening included examination of flavonoids, alkaloids, saponins, tannins, and steroids/triterpenoids. The method used to test the antioxidant activity of the ethanol extract of Rambusa stem is the DPPH free radical scavenging method, and the determination of total flavonoid and total phenol levels was carried out by experimental collection and sample processing using UV-Vis spectrophotometry. The results of phytochemical screening showed that the ethanol extract of the Rambusa stem contained flavonoids, alkaloids, tannins, and steroids/triterpenoids. DPPH shows that the ethanol extract of the Rambusa stem has an average IC50 value of 267.974% categorized as very weak. The ethanol extract of the Rambusa stem has an average total flavonoid content of 51.76283 mg QE/g and an average total phenol content of 19.3197296 mg GAE/g.